Development of potent isoflavone-based formyl peptide receptor 1 (FPR1) antagonists and their effects in gastric cancer cell models; European Journal of Medicinal Chemistry; Vol. 261 - Francavilla F. Fabio; Sarcina F. Federica; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Kirpotina L. N. Liliya Nikolaevna; Contino M. Marialessandra; Schirizzi A. Annalisa; De Leonardis G. Giampiero; Khlebnikov A. I. Andrey Ivanovich; D'Alessandro R. Rosalba; Quinn M. T. Mark; Lacivita E. Enza; Leopoldo M. Marcello (2023, 2023)
Title screen